(3eONd Edi GdJObjb GdNGQLj eY GdGTGQI Edi LhOI GdJObjbs - (3Whjd(B, (3GSeGYjd s ((3GdLRGFQ s (3OGQ CLjGd GdQbej s, 2024)
(3jJfGhd gPG GdcJGH ehVhY GdJObjb GdNGQLj, MjK jcJSj gPG GdehVhY CgejI cHjQI dOi GdHGMKjf hGdegfjjf NGUI eY GdJWhQGJ GdJj JTed gPG GdehVhY hgPG eG LYdg jJWQb Edi eONd GdJObjb HeG ajg JObjb GdMSGHGJ heYGjjQ GdJObjb hJWQb Edi egfI GdJObjb GdNGQLj aj GdLRGFQ eY GdETGQI Edi GdeYGjjQ GdLRGFQjI ddJObjb hcPdc LhOI GdJObjb GdNGQLj hOhQ GdeYGjjQ GdLRGFQjI ddJObjb aj GdJMSjf ef LhOI GdJObjb GdNGQLj (B.s
Keywords: (3GdeMGSHIs; (3eQGLYI GdMSGHGJs